Systemic sclerosis – diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part 1: diagnosis and monitoring - Krasowska, Dorota; Rudnicka, Lidia; Dańczak-Pazdrowska, Aleksandra; Chodorowska, Grażyna; Woźniacka, Anna; Lis-Święty, Anna; Czuwara, Joanna; Maj, Joanna; Majewski, Sławomir; Sysa-Jędrzejowska, Anna; Wojas-Pelc, Anna (Dermatology Review/Przegląd Dermatologiczny, 2017)
Systemic sclerosis is an immune-mediated disease characterized by a chronic and progressive course. It often leads to multiorgan failure and patient disability, and contributes to significant reduction in the quality of life. Systemic sclerosis affects the skin, subcutaneous tissue, muscles, osteoarticular system and internal organs. The complexity and diversity of clinical presentations require an individual approach and multidisciplinary collaboration both at the stage of diagnosis and treatment. Critical factors in systemic sclerosis include early diagnosis, assessment of internal organ involvement, identification of patients at potential risk of organ complications, assessment of disease dynamics and activity, and implementation of optimal therapy. Part 1 presents current recommendations for the diagnostics and monitoring of patients with systemic sclerosis. Attention is given to classification criteria, clinical forms of systemic sclerosis, assessment of skin thickness and systemic sclerosis microangiopathy, significance of antinuclear antibodies, diagnosis of interstitial lung disease and pulmonary arterial hypertension, renal crisis and cardiac abnormalities, and evaluation of the gastrointestinal tract and osteoarticular and muscular systems.